2007
DOI: 10.1002/jor.20436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extracellular osmolarity and mechanical stimulation on gene expression of intervertebral disc cells

Abstract: Intervertebral discs (IVD) have a higher extracellular osmolarity than most other tissues; moreover their osmolarity changes by around 25% during each diurnal cycle. In this study, changes in aggrecan, collagen I and collagen II expression of IVD cells were examined after exposure to osmotic environment alterations or mechanical stimulation under different osmotic conditions. Human and bovine IVD cells seeded in three-dimensional (3D) collagen type I matrices were cultured under hypo-osmotic (300 mOsm), iso-os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
143
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 30 publications
12
143
2
2
Order By: Relevance
“…Cell volume changes could affect various membrane ion transporters and alter cell metabolism, resulting in a different biosynthetic activity of the cell [35,116]. Furthermore, studies have shown that osmolality and pH directly affect IVD cell metabolism [12,18,27,37,115,129].…”
Section: Indirect Stimulusmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell volume changes could affect various membrane ion transporters and alter cell metabolism, resulting in a different biosynthetic activity of the cell [35,116]. Furthermore, studies have shown that osmolality and pH directly affect IVD cell metabolism [12,18,27,37,115,129].…”
Section: Indirect Stimulusmentioning
confidence: 99%
“…When NP cells were cultured in various osmotic conditions and exposed to the same IHP, hypo-and hyper-osmotic condition resulted in an anabolic and catabolic response, respectively [129]. This may imply that the initial volume of the cells affects their response to mechanical stimulus.…”
Section: Other Factorsmentioning
confidence: 99%
“…300 mOsm/kg H 2 O are hypo-osmotic for nucleus pulposus cells in vivo and characterize degenerated discs. 17 Extracellular osmolality of 400 mOsm/kg H 2 O, although high for cells deriving from the majority of the tissues, is considered as normal for disc cells, which are surrounded by a cation-attracting extracellular matrix. 6 500 mOsm/kg H 2 O represent hyper-osmotic conditions for disc cells, being the outcome of fluid loss due to daily activities.…”
Section: Exposure Of Cells To Different Osmotic Conditionsmentioning
confidence: 99%
“…These include the presence of growth factors, changes in local biomechanical stresses and in the osmotic environment of the disc cell [44,47,72,98,143,144,157]. Stimulation of endogenous disc cell populations by administered growth factors and other biomimetics in slow delivery carriers within bioscaffolds aim to address some of these questions [53,85].…”
Section: Cell-based Therapies For the Biologic Treatment Of Disc Degementioning
confidence: 99%